The Routledge companion to Anglophone Caribbean literature - Bucknor, Michael; Donnell, Alison, 1966- (Routledge literature companions, 2011)
The Routledge Companion to Anglophone Caribbean Literature offers a comprehensive, critically engaging overview of this increasingly significant body of work. The volume is divided into six sections that consider:the foremost figures of the Anglophone Caribbean literary tradition and a history of literary critical debate textual turning points, identifying key moments in both literary and critical history and bringing lesser known works into contextfresh perspectives on enduring and contentious critical issues including the canon, nation, race, gender, popular culture and migration new directions for literary criticism and theory, such as eco-criticism, psychoanalysis and queer studies the material dissemination of Anglophone Caribbean literature and generic interfaces with film and visual art. This volume is an essential text that brings together sixty-nine entries from scholars across three generations of Caribbean literary studies, ranging from foundational critical voices to emergent scholars in the field. The volume's reach of subject and clarity of writing provide an excellent resource and springboard to further research for those working in literature and cultural studies, postcolonial and diaspora studies as well as Caribbean studies, history and geography.